9.09.004: "Charlie Walsh being interviewed by folklore student Tanya Kearly," CD, 1995 - Kearley, Tanya; Walsh, Charles (1995)
Folklore student Tanya Kearley interviewed my father Charlie about faith healers when he was growing up in Bellevue, Trinity Bay.